Factors Influencing the Use of Communication Technology of Older People in Community for Health Care - Voraroon, Supaporn; Poltana, Pisit; Phosuwan, Akom; Jaiyungyuen, Umakorn (Journal of Nursing, Siam University, 2020)
This study aimed to investigate the predictive factors influencing the use of communication technology in older people. The dependent variables were perceived benefits of using communication technology, perceived ease of using communication technology, attitudes about using communication technologies and intention to use communication technology among the elderly. A total of 338 elderly subjects participated in the study, and the instrumentation were questionnaires that was developed by using the Technology Acceptance Model (TAM). The reliability of this questionnaire was in high level (r = .85). A descriptive statistics and hierarchical regression analysis was used to analyze the data. According to the findings, most elderly people used various kinds of communication technology to facilitate improved healthcare behaviors. Older people believed that perceived ease of using communication technology (Beta=.856, p<.001), and intention to use communication technology among the elderly (Beta=.615, p<.001), which can facilitate older people in improving their health behaviors. In conclusions, the research results show the perceive benefits and the perceived ease of using communication technology can predict an intention to use communication technology in elderly healthcare. The Implication in this research will assist health care team to apply a communication technology to improve healthcare in appropriate situation such as training knowledge via mobile device or another communication media.